2020
DOI: 10.1007/s00382-020-05231-4
|View full text |Cite
|
Sign up to set email alerts
|

Climate change projections of temperature and precipitation in Chile based on statistical downscaling

Abstract: General circulation models (GCMs) allow the analysis of potential changes in the climate system under different emissions scenarios. However, their spatial resolution is too coarse to produce useful climate information for impact/adaptation assessments. This is especially relevant for regions with complex orography and coastlines, such as in Chile. Downscaling techniques attempt to reduce the gap between global and regional/local scales; for instance, statistical downscaling methods establish empirical relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(70 citation statements)
references
References 43 publications
2
68
0
Order By: Relevance
“…However, a decrease in minimum temperature is projected in summer in the 2040s. This decrease in minimum temperature suggests a cooling from the surface water near the coast, neutralizing the warming effect [55]. The highest increase in seasonal minimum temperature is projected under SSP5-8.5 in the 2090s, with an increase of about 4.2 • C. Consistent with previous studies, we found that seasonal and annual temperatures in Africa are expected to increase rapidly than the global average in the 21st century [5].…”
Section: Future Temperaturesupporting
confidence: 89%
“…However, a decrease in minimum temperature is projected in summer in the 2040s. This decrease in minimum temperature suggests a cooling from the surface water near the coast, neutralizing the warming effect [55]. The highest increase in seasonal minimum temperature is projected under SSP5-8.5 in the 2090s, with an increase of about 4.2 • C. Consistent with previous studies, we found that seasonal and annual temperatures in Africa are expected to increase rapidly than the global average in the 21st century [5].…”
Section: Future Temperaturesupporting
confidence: 89%
“…Next steps will consider the use of both downscaled General Circulation Models and hydrological models to provide critical information at the basin scale considering the complex topography of the Andes mountains. This kind of studies has been recently developed in Brazil by Avila-Diaz et al (2020a,b), who provided information regarding the projected evolution of extreme precipitation and temperature indices, and in Chile by Araya-Osses et al (2020), who generated climate change projections of daily maximum and minimum temperature and precipitation in more than 400 locations. The outcomes of this future study will provide tailored information that can aid decision-making processes in near-term agricultural practices and water management.…”
Section: Discussionmentioning
confidence: 99%
“…The region has a population of 402,669 as per the 2015 census. Antofagasta has an average annual temperature of 16.8 • C and July is the coldest month, with an average low temperature of 11.8 • C, and an average high temperature of 16.5 • C [1]. In Chile, the Antofagasta region is called the mining industry s heart, generating 53% of the mining output, led by copper and followed by potassium nitrate, gold, iodine, and lithium in the area.…”
Section: Study Areamentioning
confidence: 99%
“…Chile has a boundary with Peru in the north, Bolivia in the northeast, Argentina in east, and the Pacific Ocean in the west. Chile is divided into 16 regions and has a diverse climate, such as northern region belongs to world s driest desert with a semi-arid climate, the center region of the country belongs to a Mediterranean climate, Easter Island has humid subtropical climate and east and south regions including alpine tundra and glaciers are belong to oceanic climate [1]. Chile has four significant seasons, summer from January to March, autumn during the April to June, winter during the July to September, and spring during the October to December.…”
Section: Introductionmentioning
confidence: 99%